2019
DOI: 10.2139/ssrn.3463275
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sitagliptin on Endometrial Mesenchymal Stem-Like Progenitor Cells: A Randomised, Double-Blind Placebo-Controlled Feasibility Trial

Abstract: Background: Recurrent pregnancy loss (RPL) is associated with the loss of endometrial mesenchymal stem-like progenitor cells (eMSC). DPP4 inhibitors may increase homing and engraftment of bone marrow-derived cells to sites of tissue injury. Here, we evaluated the effect of the DPP4 inhibitor sitagliptin on eMSC in women with RPL, determined the impact on endometrial decidualization, and assessed the feasibility of a full-scale clinical trial. Methods: A double-blind, randomised, placebo-controlled feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…In this context, a recent pilot trial demonstrated that sitagliptin, a dipeptidyl-peptidase IV inhibitor used in the management of diabetes, increases endometrial clonogenicity and decreases decidual senescence during the implantation window in recurrent miscarriage patients. 74 The efficacy of sitagliptin, and other potential interventions that target BDMSC and decidual precursor cells, 28 in mitigating the risk of adverse pregnancy outcome warrants further evaluation in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a recent pilot trial demonstrated that sitagliptin, a dipeptidyl-peptidase IV inhibitor used in the management of diabetes, increases endometrial clonogenicity and decreases decidual senescence during the implantation window in recurrent miscarriage patients. 74 The efficacy of sitagliptin, and other potential interventions that target BDMSC and decidual precursor cells, 28 in mitigating the risk of adverse pregnancy outcome warrants further evaluation in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, recurrent pregnancy loss, defined as multiple miscarriages, is associated with loss of endometrial clonogenicity (Lucas et al, 2016, Diniz-da-Costa et al, In press), uNK cell deficiency and excessive decidual senescence (Lucas et al, 2020, Tewary et al, 2020), and rapid conceptions (also referred to as ‘superfertility’) (Dimitriadis et al, 2020, Ticconi et al, 2020). Conversely, lack of a proliferative gene signature in midluteal endometrium and premature expression of decidual PRL have been linked to recurrent implantation failure (Berkhout et al, 2020b, Koler et al, 2009, Koot et al, 2016), a pathological condition defined by a failure to achieve a pregnancy following transfer of one or more high-quality embryos in multiple IVF cycles (Polanski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Turnover of senescent decidual cells likely promotes recruitment of bone marrow-derived decidual precursor cells, which confer tissue plasticity for rapid decidual expansion in early pregnancy (Diniz-da-Costa et al, In press). Importantly, lack of clonogenic decidual precursor cells and a pro-senescent decidual response are linked to recurrent pregnancy loss (Lucas et al, 2016, Lucas et al, 2020, Tewary et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring from first detection has the potential to be useful in cases of recurrent miscarriage, particularly as research into treatment gains traction. A recently published feasibility study assessing the effectiveness of the diabetes drug sitagliptin as a treatment for recurrent miscarriage, presented promising findings 24 . This trial builds on previous research, which found that in some cases of recurrent miscarriage it is the deterioration of stem-like cells in the uterus which contribute to pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%